Faktor yang Mempengaruhi Kepatuhan Ibu Hamil dalam Melakukan Kunjungan Antenatal Care (ANC) di Layanan Kesehatan - Setiyorini, Ana; Yuliana Sijabat , Friska; Anita Sari , Maudy (I Care Jurnal Keperawatan STIKes Panti Rapih, 2021)
Background: Antenatal care (ANC) is a health service from professionals for pregnant women in accordance with service standards that implemented to improve the physical and mental health of pregnant women optimally, so that they able to face childbirth, postpartum periode, exclusive breastfeeding preparation, and periode of reproductive system return to its normal pre-pregnant stage. Mother’s adherence in ANC attendance can detect and treat pregnancy problems which could impact on maternal mortality. Inadequate utilization of health services can be caused by many factors, including knowledge of pregnant women, distance of residence, family income, information from media, family support, and health workers’ factor. Objective: Determined the factors that influence the adherence of pregnant women to ANC attendance at Panti Rini Hospital Yogyakarta Method: This research is a descriptive analytic study with a cross sectional design at Panti Rini Hospital Yogyakarta. The sample in this study were thirty-two of third trimester pregnant women who visited antenatal care during 15 December 2020-6 January 2021 which recruited with an accidental sampling. Univariate, bivariate analysis with the Spearman correlation statistical test used to determine the relationship of each variables (p-value) at the level of significance p <0.05. Results: Factors that influence maternal adherence to ANC attendance were family support (p-value: 0,000). The factors that did not affect were maternal age (p-value: 0.868), maternal education (p-value: 0.644), employment status (p-value: 0.224), maternal knowledge (p-value: 0.175), distance of residence (p-value: 0.613), family income (p-value: 0.921), media information (p-value: 0.233), support from officers (p-value: 0.141). Conclusions: Factors that influence maternal adherence to ANC attendance were family support. The factors that did not affect were maternal age, maternal education, employment status, maternal knowledge, distance of residence, family income, media information, support from officers. It is hoped that the family will always offer support the mother in checking her pregnancy.